2018
DOI: 10.3390/app8071020
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Copper Nanoparticles Increases the Fruit Quality and the Content of Bioactive Compounds in Tomatoes

Abstract: Nanotechnology is a potential and emerging field with multiple applications in different areas of study. The beneficial effects of the use of nanoparticles in agriculture have already been proven. The objective of this research was to determine if the foliar application of Cu nanoparticles (NPs) could increase the content of the bioactive compounds in tomato fruits. Our study considered four treatments with different concentrations of Cu nanoparticles (50, 125, 250, 500 mg L −1 , diameter 50 nm) applied twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(101 citation statements)
references
References 70 publications
10
81
3
2
Order By: Relevance
“…The application of Cu NPs increased the content of flavonoids and glutathione in tomato fruits by 36.14% [42], coinciding with what is observed here. The application of Cu NPs + chitosan in tomato plants increased the lycopene content in fruits by 12% [43], an effect that was not observed here with the application of Se NPs and Cu NPs.…”
Section: Discussionsupporting
confidence: 88%
“…The application of Cu NPs increased the content of flavonoids and glutathione in tomato fruits by 36.14% [42], coinciding with what is observed here. The application of Cu NPs + chitosan in tomato plants increased the lycopene content in fruits by 12% [43], an effect that was not observed here with the application of Se NPs and Cu NPs.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in ORP observed in the As-SiO 2 NPs interaction indicates a better fruit quality, since it can translate into a higher antioxidant potential [52], as observed in the correlations in this work. This trend has been reported by other authors who have worked with the application of NPs in tomato [28] and observed a decrease in ORP of 5.7% with the application of 250 mg L −1 of Cu NPs.…”
Section: Discussionsupporting
confidence: 87%
“…The parameters that describe a fruit's quality (hydrogen potential (pH), total soluble solids (TSS), fruit firmness, titratable acidity (TA), electrical conductivity (EC), and Oxide-Reduction Potential (ORP) were determined, as described in López-Vargas et al [28]. For this, six fruits per treatment (one per plant) of uniform size and in a light red state of maturity were collected from the third cluster.…”
Section: Fruit Qualitymentioning
confidence: 99%
“…[25]. In case of copper NPs, they also increase the fruit quality and bioactive compound content [26].…”
Section: Biologicallymentioning
confidence: 99%